Security analysis on a kind of group signatures - SI Tao-zhi1; WANG Ze-cheng1; LI Zhi-bin1; ZHOU Zhen-jiang1 (Tongxin xuebao, 2003)
In 1998, Lee and Chang proposed a group signature scheme based on the discrete logarithm problem.Tseng, Jan and Ao gave respectively new improved scheme based on Lee-Chang scheme. In this paper, we show there are still some security leaks in these schemes, and give some methods of forgery attack.